A review of the relationships between drought and forest fire in the United States. (19th April 2016) - Littell, Jeremy S.; Peterson, David L.; Riley, Karin L.; Liu, Yongquiang; Luce, Charles H.
Abstract: The historical and presettlement relationships between drought and wildfire are well documented in North America, with forest fire occurrence and area clearly increasing in response to drought. There is also evidence that drought interacts with other controls (forest productivity, topography, fire weather, management activities) to affect fire intensity, severity, extent, and frequency. Fire regime characteristics arise across many individual fires at a variety of spatial and temporal scales, so both weather and climate – including short‐ and long‐term droughts – are important and influence several, but not all, aspects of fire regimes. We review relationships between drought and fire regimes in United States forests, fire‐related drought metrics and expected changes in fire risk, and implications for fire management under climate change. Collectively, this points to a conceptual model of fire on real landscapes: fire regimes, and how they change through time, are products of fuels and how other factors affect their availability (abundance, arrangement, continuity) and flammability (moisture, chemical composition). Climate, management, and land use all affect availability, flammability, and probability of ignition differently in different parts of North America. From a fire ecology perspective, the concept of drought varies with scale, application, scientific or management objective, and ecosystem.